The Influence of Marketing Communication on Consumer Interest in BNKP PLKTIN Gunungsitoli - Ratna sari Lase; Idarni Harefa; Yupiter Mendrofa; Otanius Laia (Sean Institute, 2025)
Marketing communication is a means by which companies try to inform, persuade and remind consumers directly or indirectly about the products and brands being marketed.This study aims to determine the effect of marketing communication on consumer interest in PLKT BNKP in Gunungsitoli. Effective marketing communication can increase consumer interest and influence their purchasing decisions. This study uses a quantitative method with data analysis techniques using SPSS to determine how much influence it has. The sample in this study was 30 respondents, namely employees and customers at PLKT. The results of the study showed that there was an effect of marketing communication on consumer interest in PLKT in Gunungsitoli, namely where the test of variables X and Y was declared valid because the result of the calculated r of 0.742 was greater than the r table, which was 0.361. In addition, the large influence of marketing communication was obtained by an average respondent answer of 6.42 with good criteria. Consumer interest in PLKT was obtained by an average respondent answer of 7.24 with good criteria. Thus, marketing communication has a significant influence on consumer interest. This means that marketing communication has an effect on consumer interest so that it can increase profits for the company. These findings suggest that an effective marketing communication strategy is the key to increasing overall consumer interest.